2015
DOI: 10.3342/ceo.2015.8.3.211
|View full text |Cite
|
Sign up to set email alerts
|

Cordblood-Based High-Throughput Screening for Deafness Gene of 646 Newborns in Jinan Area of China

Abstract: ObjectivesInfants with slight/mild or late-onset hearing impairment might be missed in universal newborn hearing screening (UNHS). We identified the mutation hot spot of common deaf gene in the newborns in Jinan area population by screening the mutation spot with neonate cord blood, in order to make clear whether the neonate cord blood for screening is feasible.MethodsSix hundred and forty-six newborns were subjected to both UNHS and genetic screening for deafness by using neonate cord blood. The newborn genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Thus, with cost-effective and rapid turnaround, the screening of large populations is feasible. Here, it should be noticed that the next-generation sequencing provides a stronger solution [ 10 , 14 ],whereas organizing massive population genetic screening is challenging, which also increases interpretation burden. In addition, the microarray platform shows excellent detection sensitivity to the heteroplasmic mitochondrial variants.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, with cost-effective and rapid turnaround, the screening of large populations is feasible. Here, it should be noticed that the next-generation sequencing provides a stronger solution [ 10 , 14 ],whereas organizing massive population genetic screening is challenging, which also increases interpretation burden. In addition, the microarray platform shows excellent detection sensitivity to the heteroplasmic mitochondrial variants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the feasibility of concurrent hearing and genetic screening. [7][8][9][10][11] However, the benefits of such practices have not been quantified due to limited sample sizes and outcome data. Herein we report results of genetic screening on~1.2 million newborns in China and outcomes of 12,778 infants with genetic findings followed up via phone interviews.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated the feasibility of concurrent hearing and genetic screening. 711 However, the benefits of such practices have not been quantified due to limited sample sizes and outcome data. Herein we report results of genetic screening on ∼1.2 million newborns in China and outcomes of 12,778 infants with genetic findings followed-up via phone interviews.…”
Section: Introductionmentioning
confidence: 99%